High-throughput Photoactive Magnetic Microrobots for Food Quality Control - Maria-Hormigos, Roberto; Mayorga-Martinez, Carmen C; Kim, Jeonghyo; Pumera, Martin (Small methods, 2025)
Ensuring food quality and safety according to stringent global standards requires analytical procedures that are accurate, cost-effective, and efficient. This present innovative high-throughput microrobots designed for the detection of antioxidants in food samples. These microrobots consist of photocatalytic bismuth subcarbonate anchored on silica-coated magnetite nanoparticles. Upon exposure to UV light, they generate reactive oxygen species via photocatalysis, which oxidize the colorless dye into a green-colored radical cation. The presence of antioxidants inhibits this reaction, allowing for the quantification of antioxidant activity. The magnetic Fe₃O₄/SiO₂ core enables steering of the microrobots using a transverse rotating magnetic field, facilitating automated assays on a custom-designed 3D-printed sensing platform. This results demonstrate that these magneto-photocatalytic microrobots can perform automated, high-throughput assessments of food quality, representing a significant advancement in food analysis technology.
Keywords: Robotics; Food Quality; nanorobots; řízení kvality; rychlé screeningové testy; Silicon Dioxide; Antioxidants; ultrafialové záření; microrobots; antioxidancia; Quality Control; Food Analysis; food analysis; oxid křemičitý; kvalita jídla; magnetické nanočástice; Ultraviolet Rays; analýza potravin; High-Throughput Screening Assays; Magnetite Nanoparticles; robotika